Magnitude, Nature, and Risk Factors of Adverse Drug Reactions Associated with First Generation Antipsychotics in Outpatients with Schizophrenia: A Cross-Sectional Study - Bahta M; Berhe T; Russom M; Tesfamariam EH; Ogbaghebriel A (Dove Medical Press, 2020)
Merhawi Bahta,1 Tzeggai Berhe,2 Mulugeta Russom,3 Eyasu H Tesfamariam,4 Azieb Ogbaghebriel5 1School of Pharmacy, Asmara College of Health Sciences, Asmara, Eritrea; 2Department of Addictions and Mental Health, University of Alberta, Edmonton, Canada; 3Eritrean Pharmacovigilance Centre, National Medicines and Food Administration, Asmara, Eritrea; 4Biostatistics and Epidemiology Unit, Department of Statistics, College of Science, Eritrean Institute Technology, Asmara, Eritrea; 5College of Pharmacy, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Merhawi BahtaSchool of Pharmacy, Asmara College of Health Sciences, Asmara, EritreaTel +291-7294279Email meramcp19@gmail.comBackground: ADRs to antipsychotics are amongst the major challenges in the treatment of patients with psychotic disorders. The extent of patient-reported ADRs assessed in many studies using standardized scales is found to be inconsistent. However, there is a paucity of such research in Eritrea. The aim of the study is therefore to determine the magnitude, nature, and the possible risk factors associated with ADRs of the first generation antipsychotics in outpatients with schizophrenia at Saint Mary Neuro-Psychiatric National Referral Hospital in Asmara, Eritrea, using the LUNSERS self-rating scale.Methods: A cross-sectional, descriptive and analytical study design utilizing a quantitative approach was employed. Data were collected from patients’ self-administered questionnaires, interviews, and medical records. The collected variables were analyzed using SPSS 22.0 with descriptive statistics, correlation, t-tests, ANOVA, and multiple regression. Statistical significance was tested at P-value< 0.05.Results: In this study, 93.8% of the research participants experienced at least one ADR. LUNSERS total mean score of the relevant items was 28.01 (SD=18.46) with 24.7% of the study participants scoring medium-to-high. The prevalence of the categories of ADRs was psychic (91.3%), autonomic (78.1%), extra-pyramidal (76.9%), miscellaneous (66.5%), hormonal (58.3%), anti-cholinergic (44.2%), and allergic reactions (44.2%). At multivariate level, factors significantly and positively associated with total ADR score were smoking (P=0.028) and being at secondary educational level (P=0.015).Conclusion: There was high prevalence of ADRs with moderate-to-high overall ADR scores in a significant number of patients. The most frequently reported ADRs were psychic, autonomic, extra-pyramidal, hormonal, and miscellaneous. Smoking and secondary level of education were found to be the main determinants of ADRs.Keywords: schizophrenia, first generation antipsychotics, adverse drug reactions, LUNSERS, risk factors